1996
DOI: 10.2172/270452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of irradiation spectrum and implanted ions on the amorphization of ceramics

Abstract: Polycrystalline specimens of alumina (Al2O3), magnesium aluminate spinel (MgA1204), magnesia (MgO), silicon nitride (Si3N4) and silicon carbide (Sic) were irradiated with various ions at temperatures between 200 K and 450 K, and the microstructures were examined following irradiation using cross-section transmission electron microscopy. Amorphization was not observed in any of the irradiated oxide ceramics, despite damage energy densities up to-7 keV/atom (-70 displacements per atom). On the other hand, Sic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…Maximum values of Al and O damage peaks appeared at a flux of 1.9 · 10 17 ions/m 2 s. RBS/ channeling measurements indicated that spinel was not completely amorphized over the flux range examined, although the crystalline lattice is significantly damaged. This result agrees with several studies of spinel irradiated with lower flux at room temperature [24,25]. The resistance of spinel against amorphization at high-flux may also arise from the recombination of radiation-induced interstitials with structural vacancies in the spinel structure.…”
Section: Resultssupporting
confidence: 92%
“…Maximum values of Al and O damage peaks appeared at a flux of 1.9 · 10 17 ions/m 2 s. RBS/ channeling measurements indicated that spinel was not completely amorphized over the flux range examined, although the crystalline lattice is significantly damaged. This result agrees with several studies of spinel irradiated with lower flux at room temperature [24,25]. The resistance of spinel against amorphization at high-flux may also arise from the recombination of radiation-induced interstitials with structural vacancies in the spinel structure.…”
Section: Resultssupporting
confidence: 92%
“…In order to implement the ion-implantation based doping process for silicon carbide, previous works [1][2][3][4]10] mainly concentrated on the irradiation with ions of medium mass having energies of a few hundreds keV, i.e. in a slowing down regime where the nuclear energy loss is dominant.…”
Section: Irradiations With Low Energy Ionsmentioning
confidence: 99%
“…It is worth mentioning that several review papers were published in the 90's [1][2][3][4] on ion implantation effects and ion beam processing of SiC at low energy. These investigations mainly deal with defect formation [5], amorphization and annealing [1], recrystallization [6,7] and electrical activation of dopant atoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Electron irradiation studies were not included in the estimation of the critical interstitial migration temperature, due to possibly large effects of ionization-induced diffusion [41]. To the authors knowledge there are no data from which the critical temperature for interstitial migration in silicon nitride can be accurately determined, though it can be inferred to be <80 K based on the resistance of Si 3 N 4 to ion beam-induced amorphization at 80 K up to a dose level of 30 dpa [74].…”
Section: Summary Of Dose and Materials Dependence Of Thermal Resistancementioning
confidence: 99%